Literary Heritage of Bosnian Muslims Written in Oriental Languages in Light of European Oriental Studies - Filipović, Nenad (Prilozi za orijentalnu filologiju, 2017)
The present paper is the author’s review of the works concerning literary heritage of the Bosnian Muslims which were written by European orientalists. The author’s intention was not to give a bibliographical inventory of the data about ali the relevant works, but to present metodological development of that studies in Europe, and to mark the noticable differences in the European stan- dpoint of the heritage in question. A survey of the beginning of the researches is given, as well as the revievv of the most important philological works (catalogues and critical edition), monographies and articles treating this problem. As for the oriental studies literature, the fırst revievvs of the literary works of Bosnian Muslims are fo- und in the great historical surveys of Turkish poetry and Arabic literature written by Hammer, Gibb and Brockelmann. Among the monographies pub- lished in Europe two are distinguished: J. Rypka’s monography about Sabit of Užice, from 1924, and the book of Jasna Šamić about Hasan Khaimi-baba, from 1986. Up to the Alexandre Popović’s works, European oriental studies have tre- ated these literary vvorks as an integral part of the Ottoman literature. Popović started a number of metodological questions concerning the study of this literature. Apart from that, he is being engaged for a many years in the all-inclusive prosographical and literary-historical researches of the literature written in oriental languages in South-East Europe and Balkans.